TANGGUNG JAWAB DEVELOPER YANG WANPRESTASI DALAM PERJANJIAN PENGIKATAN JUAL BELI PERUMAHAN - Widhy Andrian Pratama; Halimah Endang Widyaningsih (Jurnal Jendela Hukum, 2025)
The implementation of landed house construction by developers still relies on conventional construction methods or on-site construction. This method is a construction technique that has long been known and widely used, and is supported by the availability of experts and construction service providers who are competent in planning and implementation. However, this method is not free from weaknesses, including uncertainty in determining the technical specifications of the building accurately. In addition, the implementation process also has the potential to experience increased costs, especially when disrupted by external factors such as uncertain weather conditions. This article uses a normative approach, which focuses on the analysis of law as a system of rules that are binding and serve as guidelines in community life. Therefore, the normative legal approach focuses on the analysis of positive law, legal principles and doctrines, legal interpretation in concrete cases, the structure of the legal system, harmonization of legal norms, comparative legal studies, and historical aspects of the legal system being studied. This research is descriptive-analytical. From this research, it can be concluded that the legal implications of the implementation of the pre-project selling system arise when business actors do not carry out their obligations as determined, so that it can cause objections or complaints from consumers if the results received are not in accordance with the agreement in the sale and purchase contract. In an agreement, a business actor is said to have made an achievement if he is able to carry out his obligations properly. Conversely, if he fails to carry out his responsibilities, then this condition is called a breach of contract. A breach of contract is a form of non-compliance with an agreement that has been agreed upon, and this gives the injured party the right to claim compensation as a form of accountability for the violation